Waqf Law is Relevant in Responding to the Challenges of the Age Regarding the Law of Selling Waqf Goods: Study of the Book of Fathul Mu'in by Syaih Zainuddin Bin Abdul Aziz Al-Malibari - Waluyo Waluyo (Universitas Wiralodra, 2023)
This study aims to provide a deeper understanding and offer solutions to the statements in the book. The research method used is qualitative research with a normative legal approach or library research. Contextual analysis was carried out to understand and analyze in depth the contents of the book